1980
DOI: 10.5962/bhl.title.42365
|View full text |Cite
|
Sign up to set email alerts
|

Purification, partial characterization, and serology of the capsid and cylindrical inclusion proteins of four isolates of watermelon mosaic virus / by Robert H. Baum.

Abstract: WMV-1 and WMV-2 Defined Antisera specific for the cylindrical inclusions of WMV-M, WMV-1, and WMV-2 in SDS immunodiffusion cests with sap and purified inclusions were obtained. Antisera to WMV-2 inclusions reacted heterologously with BCMV, dasheen mosaic virus (DMV) , soybean mosaic virus (SoyMV) and lettuce mosaic virus (LMV). WMV-M inclusion antiserum reacted heterologously with WMV-1, WMV-2, DMV, and PRSV and with some isolates of LMV. The WMV-1 inclusion antiserum did not react with either WMV-M or WMV-2 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Detailed comparative studies of the host range, behaviour towards resistance genes in melons, and serological properties of coat protein, cylindrical inclusion protein, and amorphous inclusion protein of a large number of isolates of WMVMorocco, PRSV-W, ZYFV, ZYMV, and WMV 2 obtained from different countries showed that the isolates of WMV-Morocco were closely related to those of PRSV-W [3,24,25]. However, other investigations of biological properties, peptide mapping of protease V 8 digests in SDS-PAGE and serological relationships of coat protein and cylindrical inclusion protein using antisera to the Florida isoaltes of PRSV-W and WMV 2 suggested that WMV-Morocco is distinct from PRSV-W and WMV 2 [4][5][6]20].…”
mentioning
confidence: 99%
“…Detailed comparative studies of the host range, behaviour towards resistance genes in melons, and serological properties of coat protein, cylindrical inclusion protein, and amorphous inclusion protein of a large number of isolates of WMVMorocco, PRSV-W, ZYFV, ZYMV, and WMV 2 obtained from different countries showed that the isolates of WMV-Morocco were closely related to those of PRSV-W [3,24,25]. However, other investigations of biological properties, peptide mapping of protease V 8 digests in SDS-PAGE and serological relationships of coat protein and cylindrical inclusion protein using antisera to the Florida isoaltes of PRSV-W and WMV 2 suggested that WMV-Morocco is distinct from PRSV-W and WMV 2 [4][5][6]20].…”
mentioning
confidence: 99%